FORAMINIFERI ATTUALI IN SEDIMENTI INFRALITORALI E CIRCALITORALI A NORD DI MESSINA (SICILIA, ITALIA) - GABRIELLA MANGANO; DONATA VIOLANTI (Rivista Italiana di Paleontologia e Stratigrafia, 2017)
Quantitative micropaleontological analyses are carried out on eleven samples from inner neritic to outer neritic sands of the sicilian coast, north of Messina. Three groups are described: 1) fossil taxa, mainly from Pliocene sediments in the terrigenous discharges, 2) live and 3) dead specimens of recent species. The distribution of benthic specimens seems largely controlled by the amounts and the sites of terrigenous sediments deposition and by the patchiness of algal biocoenoses. Percentages of live forms are higher in the northern samples, less affected by reworked or winnowed sediments: sessile foraminifers (Glabratellidae, Discorbidae) are dominant. On the contrary, dead specimens of miliolids, elphidiids, rare rotaliids ecc. are common in the thanatocoenoses of the southern and deeper samples.